Camouflage orthodontic treatment of class I malocclusion with bimaxillary prognathism and risk of apical tooth resorption: a case report - arlan, Anggi; Anggani, Haru Setyo; Antolis, Maureen; Develas, Deo (Jurnal Kedokteran Gigi Universitas Padjadjaran, 2024)
Introduction: The primary goal of orthodontic treatment for bimaxillary prognathism is to reduce facial convexity. Treatment options depend on skeletal discrepancies and may involve surgery combined with orthodontics or camouflage orthodontic treatment. However, camouflage orthodontic treatment in cases of severe skeletal discrepancies carries a risk of root resorption. This case report aims to present the orthodontic camouflage treatment of Class I bimaxillary prognathism and its associated risk of root resorption. Case report: A 19-year-old female patient presented with a chief complaint of lower teeth crowding. She had a dolichofacial, symmetrical, and balanced face with a convex profile. The relation of incisor and canine on both the right and left sides was Class I.  The first molar relation of the right side is class I, and the left is class III with 3 mm overjet and 4 mm overbite. The lower midline shifted 2 mm to the left. Spaces requirement of the treatment based on Kesling’s method was a final overjet of 2 mm as follows: Upper Right -4.5 mm, Upper Left -4 mm, Lower Left -5 mm, and Lower right -4 mm. Treatment indication was camouflage orthodontic treatment with extraction using pre-adjusted edgewise MBT 0.022” brackets. The treatments aim to camouflage the convex profile caused by prognathism in both jaws and the degree of protrusion of the maxillary and mandibular anterior teeth. Conclusion: The orthodontic camouflage treatment for Class I bimaxillary prognathism using extractions and fixed appliances with preadjusted edgewise MBT 0.022” brackets improved facial and smile aesthetics, as well as masticatory function. However, Root resorption occurred as a complication due to maxillary and mandibular incisor intrusion during deep overbite correction over 27 months of treatment.Perawatan ortodonti kamuflase kasus maloklusi kelas I bimaxillary prognathism dan risiko resorpsi akar gigi: laporan kasusPendahuluan: Tujuan utama perawatan ortodonti kasus bimaxillary prognathism adalah mereduksi kecembungan profil wajah pasien. Pilihan perawatan ortodonti kasus bimaxillary prognathism berdasarkan diskrepansi skeletal dapat berupa perawatan kombinasi bedah dan ortodonti atau perawatan ortodonti kamuflase. Tujuan laporan kasus ini adalah melaporkan perawatan ortodonti kamuflase kasus maloklusi kelas I bimaxillary prognathism dan risiko resorpsi akar gigi. Laporan kasus:  Pasien perempuan 19 tahun dengan keluhan gigi bawah tumbuh tidak beraturan. Wajah dolichofacial, simetris dan seimbang dengan profil cembung. Relasi insisif serta kaninus kanan dan kiri kelas I. Relasi molar pertama tetap kanan kelas I dan kiri kelas III dengan overjet 3 mm dan overbite 4 mm. Garis tengah lengkung gigi bawah bergeser ke kiri 2 mm. Kebutuhan ruang menurut metode kesling dengan overjet akhir 2mm sebagai berikut: kanan atas -4,5 mm, kiri atas -4 mm, kiri bawah -5 mm, dan kanan bawah -4 mm. Perawatan ortodonti kamuflase indikasi ekstraksi dengan piranti cekat preadjusted edgewise MBT slot .022”. Tujuan perawatan kasus ini adalah menyamarkan gambaran profil cembung yang disebabkan oleh prognathism pada kedua rahang serta derajat protrusi gigi - gigi anterior rahang atas dan bawah. Paska debonding ditemukan adanya resorpsi akar pada apikal gigi insisif rahang atas dan rahang bawah. Simpulan: Perawatan ortodonti kamuflase kasus maloklusi kelas I bimaxillary prognathism dengan ekstraksi dan piranti cekat braket preadjusted edgewise MBT slot 022”. memberikan perbaikan estetika/profil wajah dan senyum serta mastikasi pasien. Resorpsi akar yang terjadi merupakan komplikasi akibat dari gerakan intrusi insisif rahang atas dan rahang bawah dalam rangka koreksi deep overbite selama 27 bulan perawatan.